Coagulation in liver surgery: an observational haemostatic profile and thromboelastography study. Issue 6 (26th May 2020) - Oo, June; Allen, Megan; Loveday, Benjamin P. T.; Lee, Nora; Knowles, Brett; Riedel, Bernhard; Burbury, Kate; Thomson, Benjamin
Abstract: Background: International normalized ratio (INR) is used as a marker of the haemostatic status following liver resection. However, the impact of liver resection on haemostasis is complex and beyond what can be measured by INR. This study aimed to prospectively assess haemostatic profile following liver resection and determine if INR measurement can safely guide post‐operative thromboprophylaxis. Methods: In this prospective cohort study, patients undergoing liver resection had coagulation parameters (International normalised ratio (INR), prothrombin time (PT), activated partial thromboplastin time, fibrinogen, d‐dimer, von Willebrand factor antigen, procoagulant activity of phospholipids and clotting factors II, VII, VIIIc, IX and X) and thromboelastogram parameters assessed perioperatively. Clinical follow‐up assessed for thromboembolism and haemorrhage. Results: In the 41 patients included, INR was significantly ( P < 0.0001) elevated post‐operatively, and INR >1.5 was observed in seven of 41 (17.1%) on post‐operative day 1 and one of 41 (2.4%) patients on post‐operative day 3, respectively. Factor VII levels showed transient reduction but other factors, especially factors II and X, remained within normal range following liver resection. Thromboelastogram parameters remained normal or supranormal for all patients at all time points. One incident of post‐hepatectomy haemorrhage occurred, despite a normal coagulation profile. Two patients suffered late pulmonary embolic episodes. Conclusion: Post liver resection haemostasis is complex and poorly reflected by INR, which should not guide initiation of chemical thromboprophylaxis in the immediate post‐operative period. Abstract : The overall haemostatic potential for patients post liver resection is complex, and cannot be reduced to a single laboratory measurement such as international normalized ratio (INR). INR does increase after liver resection, although still usually remains below 1.5. Even when INR is >1.5, the ability to form a stable clot on thromboelastography remains intact. Therefore, INR should not be used to guide decision to institute pharmacological thromboprophylaxis after liver resection, particularly in the immediate post‐operative period.